Innovative Tech-Savvy Education: Designing a Smart Assessment System - Syaiful Islami; Ambiyar Ambiyar; Sukardi Sukardi; Anggi Agni Zaus; Anggun Agni Zaus; Mahesi Agni Zaus (Journal of Applied Engineering and Technological Science (JAETS), 2024)
The purpose of this research is to create a smart assessment system linked to a project-based learning model through a website. It is anticipated that this system will raise the proficiency and productivity of learning evaluation through the implementation of digital technology. The approach applied in this research includes the identification of needs, and the designing of the system, followed by software development and testing. According to the findings of the research, it is evident that the system developed for smart assessment can offer several complex and combined assessment facilities within the system, which would help the educators for easier examination of the student’s performance on a real-time basis. In addition to that, this system also enhances the common work of the students with the educators on completing the project assigned by the latter. Hence, the incorporation of website-based online assessments tries to extend the validity of the PBL implementation approach as well as contribute positively towards embracing positive enhancement in education.